Validation of AI-based semen analysis by urologists in training: clinical impact after varicocelectomy - Russo, Giorgio Ivan; Salvaggio, Antonio; Asmundo, Maria Giovanna (Frontiers in Urology, 2025)
We conducted a prospective, single-center study (IRB 17/2025) to validate an AI-enabled, computer-assisted semen analyzer (LensHooke® X1 PRO) operated by third- and fourth-year urology residents for the perioperative assessment of men undergoing loupe-assisted varicocelectomy at the University of Catania. The analyzer captured conventional and kinematic semen parameters according to the World Health Organization (WHO) 6th edition the day before and 3 months after surgery. In 42 patients (median age 31.5 years), the computer-assisted semen analysis (CASA) produced rapid, standardized readouts and showed statistically significant postoperative improvements across multiple parameters (p < 0.05). These findings support its concordance with manual analysis and underscore the value of integrating AI-based semen analysis into residency training to enhance accuracy, efficiency, and clinical decision-making in male infertility care.